2007
DOI: 10.1007/s00125-007-0637-9
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic deletion of insulin receptor substrate 2 reduces beta and alpha cell mass and impairs glucose homeostasis in mice

Abstract: Aims/hypothesis Insulin signalling pathways regulate pancreatic beta cell function. Conditional gene targeting using the Cre/loxP system has demonstrated that mice lacking insulin receptor substrate 2 (IRS2) in the beta cell have reduced beta cell mass. However, these studies have been complicated by hypothalamic deletion when the RIPCre (B6.Cg-tg(Ins2-cre) 25Mgn/J) transgenic mouse (expressing Cre recombinase under the control of the rat insulin II promoter) is used to delete floxed alleles in insulin-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 34 publications
3
62
1
Order By: Relevance
“…Studies on these disruptions suggest that, similar to the observations on beta cell hyperplasia in insulin resistance, an increase in alpha cell proliferation and hormone production occurs in states of glucagon resistance. In addition, the contribution of hyperinsulinaemia to alpha cell hyperplasia is supported by observations that IRS2 KO mice exhibit reduced alpha cell mass and glucagon secretion [69], while in vitro insulin treatment of alpha TC1 cells leads to increased alpha cell proliferation by triggering mTOR [78].…”
Section: Adulthoodmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies on these disruptions suggest that, similar to the observations on beta cell hyperplasia in insulin resistance, an increase in alpha cell proliferation and hormone production occurs in states of glucagon resistance. In addition, the contribution of hyperinsulinaemia to alpha cell hyperplasia is supported by observations that IRS2 KO mice exhibit reduced alpha cell mass and glucagon secretion [69], while in vitro insulin treatment of alpha TC1 cells leads to increased alpha cell proliferation by triggering mTOR [78].…”
Section: Adulthoodmentioning
confidence: 93%
“…Insulin/IGF-1 and glucagon signalling Genetically engineered knockout and transgenic mouse models and knockdown approaches targeting one or more proteins in the insulin/IGF-1 signalling pathway, including the insulin and IGF-1 receptors [66,67], IRS-1 and IRS-2 [68,69], Akt [70], phosphoinositide 3-kinase (PI3-kinase) [71] or FOXO1 [72], point to their significant roles in the regulation of islet biology. Several groups, including ours, have reported on the significance of insulin/IGF-1 signalling in the regulation of both beta and alpha cells [66,28].…”
Section: Adulthoodmentioning
confidence: 99%
“…Islet isolation and insulin secretion assays Islets were isolated as previously described [11]. After pancreatic digestion, islets were purified using a Ficoll-Paque (GE Healthcare, Chalfont St Giles, UK) gradient.…”
Section: Methodsmentioning
confidence: 99%
“…However, activated insulin signaling is considered to induce ␣-cell proliferation based on the findings from ␣-cell-specific insulin receptor knock-out (␣IRKO) mice and pancreas-specific IRS2 knockout mice (20,21). A recent study also demonstrated that insulin stimulates ␣-cell proliferation through the IR/IRS2/AKT/ mTOR (mammalian target of rapamycin) signaling pathway (22).…”
mentioning
confidence: 99%